2008
DOI: 10.22358/jafs/66633/2008
|View full text |Cite
|
Sign up to set email alerts
|

A note on the effects of selected prebiotics on the performance and ileal microbiota of broiler chickens

Abstract: The objective of the experiment was to study the infl uence of lactose, inulin, and modifi ed β-glucan as additives to maize-based diets on the performance of broiler chickens, as well as on the pH in the crop, gizzard, ileum, caeca and on populations of selected ileal microfl ora species. Over the entire experimental period (day 1 -day 42), the animals (384 male broilers, 4 treatments, 12 replicates of 8 birds per treatment) were offered maize-based diets. The diets were fed either without any supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 14 publications
2
28
1
Order By: Relevance
“…Lowering the caecal content pH by inulin has also been shown in other studies (Józefiak et al, 2008). Because FOS is not hydrolysed by enzymes in the small intestine of monogastrics, it reaches the colon intact.…”
Section: Discussionsupporting
confidence: 73%
“…Lowering the caecal content pH by inulin has also been shown in other studies (Józefiak et al, 2008). Because FOS is not hydrolysed by enzymes in the small intestine of monogastrics, it reaches the colon intact.…”
Section: Discussionsupporting
confidence: 73%
“…We found, however, that this effect was apparent only for the 42-day period of feeding with 32 g · kg -1 WPC (1.88 g · kg -1 lactose). Similarly, Józefiak et al (2008) observed that the addition of 2 g · kg -1 lactose to the basal diet significantly decreased caecal pH in the sixth week of a chicken's life. The significant response to the WPC level providing 1.88 g · kg -1 lactose in terms of reduced pH of digesta from the whole small intestinal tract is most likely associated with fermentation in the ileum.…”
Section: Discussionmentioning
confidence: 79%
“…Inconsistent effects of adding different prebiotic carbohydrates, including lactose, on the upper intestinal tract pH, and bacterial populations, have been noted in poultry, however. Some previous reports demonstrated that ileum pH in chickens was not significantly affected by either low (0.2%) or high (4.5%) dietary lactose levels, with lower LAB counts (Józefiak et al, 2008) or with no effect on the counts of Escherichia coli, enterococci and lactobacilli (McReynolds et al, 2007). In contrast, Samli et al (2007) claimed that treatment with dried whey, in an amount equivalent to 28 g · kg -1 lactose, significantly increases the total number of LAB in the ileum of chickens.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The third tested prebiotic, beta-glucan is well established in aquaculture, and treatment with 1% to 2% w/w feed allowed for significant improvement in FCR and increased BW in marine species (Kuhlwein et al, 2014). In poultry, addition of 0.025% modified beta-glucan did not improve broiler performance apart from increased BWG in starter period of rearing (Jozefiak et al, 2008). Whereas, the inclusion of laminarin and fucoidan beta-glucans as prebiotics improved growth parameters in weaned pigs .…”
Section: Discussionmentioning
confidence: 99%